2020
DOI: 10.1039/d0sm00267d
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale biophysical model for the recruitment of actin nucleating proteins at the membrane interface

Abstract: The dynamics and organization of the actin cytoskeleton are crucial to many cellular events such as motility, polarization, cell shaping, and cell division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Gelsolin can bind to the cell membrane by PIP 2 which abrogates the gelsolin interaction with actin. Not only does the amount of phosphoinositide alter the free or actin-bound-gelsolin in cells, but also the lateral distribution of PIP 2 controls inactivation of gelsolin [49,50]. Recent studies showed that ATP competes with PIP 2 to bind with gelsolin [51,52].…”
Section: Pip 2 In Actin Dynamicsmentioning
confidence: 99%
“…Gelsolin can bind to the cell membrane by PIP 2 which abrogates the gelsolin interaction with actin. Not only does the amount of phosphoinositide alter the free or actin-bound-gelsolin in cells, but also the lateral distribution of PIP 2 controls inactivation of gelsolin [49,50]. Recent studies showed that ATP competes with PIP 2 to bind with gelsolin [51,52].…”
Section: Pip 2 In Actin Dynamicsmentioning
confidence: 99%
“…For instance, Borau and colleagues [ 320 ] focused on the mechanosensing properties of the actomyosin network. Fatunmbi and colleagues [ 321 ] focused on the recruitment of actin nucleating proteins at the membrane interface. In contrast, Hetmanski and colleagues [ 322 ] proposed a combination of distinct modeling approaches to study rear retraction dynamics of migrating cells within 3D substrates.…”
Section: Computational Models Of Cell Migrationmentioning
confidence: 99%
“…225 PIP 2 , which produces IP 3 following PLC cleavage, regulates actin-binding proteins including talin, gelsolin, ERM proteins (ezrin/radixin/moesin), formin, and actin-related protein 2/3 (ARP2/3) to mediate actin cytoskeleton dynamics. [226][227][228] A myriad of actin-binding proteins interact with PIP 2 , 229 including ERM proteins and myosin I, 230 talin, 228 formins and ARP2/3, 227 and Coronin 1A. 231 3.3.5 SOCE regulators and cytoskeletal proteins.…”
Section: [Ca 2+mentioning
confidence: 99%